PENDIDIKAN LINGKUNGAN BERBASIS ISLAM BAGI ORANG TUA SISWA MI MATHLA’UL HUDA KEBON CAU TELUK NAGA: Menumbuhkan Kesadaran Sebagai Khalifah Di Bumi - Fitriana Siregar; Muhammad Fauzan Muttaqin; Siti Jamilah; Adnan Bafaqih; Akbar Maulana (Education and Community Service Journal (EduServe), 2025)
Many parents still do not understand the role of the caliph in the context of environmental conservation. Islamic-based environmental education is an effort to instill values of care for nature grounded in the teachings of the Qur'an and Hadith. Islamic environmental education can be carried out through the inculcation of religious values relevant to ecological issues, such as living simply, conserving energy, and wisely using resources. The purpose of this community service is to build awareness and active involvement of parents of MI students in Islamic-based environmental education. The implementation method involves initial identification and observation by the community service team, followed by socialization and education on Islamic-based environmental education. The results show significant improvement in parents' understanding of their role in environmental conservation as part of worship and Islamic ethics, reflected in the difference between pretest and posttest scores. This socialization also encourages practical behavioral changes within the family environment, thereby shaping children’s ecological character from an early age. The community service strengthens synergy among schools, families, and communities in fostering a culture of cleanliness, health, and sustainable living in accordance with Islamic values. Thus, this program provides a real contribution to strengthening family education and environmental preservation from an Islamic perspective.